INSTALLATION OF CHARACTER EDUCATION VALUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT SMAI MIFTAHUL AFKAR SIDOPEKSO KRAKSAAN - Rosyid, Muhammad Ainur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Instilling the values of character education in the learning process of Islamic Religious Education at SMAI MIFTAHUL AFKAR SIDOPEKSO KRAKSAAN is motivated by the rise of teenagers who start to commit acts that are not commendable to moral degradation. Therefore it is necessary to integrate the values of character education in teenagers, especially in the learning process of Islamic Religious Education, which incidentally aims to form good morals.This study intends to address how to instil character education values in learning Islamic religious education at SMAI MIFTAHUL AFKAR SIDOPEKSO KRAKSAAN. These problems were discussed through field studies conducted at SMAI MIFTAHUL AFKAR. SMAI MIFTAHUL AFKAR was used as a data source to obtain a portrait of planting character education values in the learning process of Islamic Religious Education. The data were obtained using free interviews, observation, and documentation studies.All data were analyzed with a phenomenological approach and descriptive analysis using the logic of induction, deduction and reflection. This research shows that: the inculcation of character education values in learning Islamic Religious Education at SMAI MIFTAHUL AFKAR SIDOPEKSO KRAKSAAN is carried out using several methods, including habituation methods, exemplary methods, methods between peers, small discussion, reading aloud, and others that are adapted to the material and conditions of students. These findings provide a reference for evaluating Islamic Religious Education's learning system to form a karakul karma character.